G262 Maple syrup urine disease (MSUD) referred to tertiary services before and after newborn screening (NBS). (May 2019) - MacGloin, H; Guilder, L; Cleary, M; Davison, J; Uudelepp, M; Chakrapani, A
Abstract : Aims: MSUD is an inherited metabolic condition, caused by BCKD (branched-chain ketoacid dehydrogenase) complex deficiency. Although rare, mimicry of presentation makes MSUD a condition of interest to the general paediatrician. Neurological presentation is variable and catastrophic in the classical form with infantile toxic encephalopathy. However outcome can be improved by early diagnosis and treatment. NBS (Newborn Screening) for MSUD was introduced nationally in 2013. We aimed to assess the impact of screening on MSUD time to diagnosis and outcome for cases referred to tertiary metabolic services. Methods: We retrospectively analysed the demographics, presentation, biochemical data, clinical management and outcome of all MSUD cases diagnosed within the data capture period: September 2000–2018. Exclusion criteria were cases older than 18 years (n=8), Type E3 variants (n=2) and prematurity with neonatal encephalopathy (n=2). Results: 23 met inclusion criteria: 11 were diagnosed by NBS, 9 were clinical diagnoses, and 3 were prospective diagnoses. MSUD diagnosed by NBS: Of this cohort, 3 neonates (27.2%) were asymptomatic and 8 neonates (72.7%) were hospitalised with symptoms at the time of screening result. Median age of symptoms was 5 days (1–8 days); median age of diagnosis was 8 days (7–12 days). Peak median leucine level was 2873 umol/L (360–4307). 8 received dialysis (72.7%) and 3 (27.2%) managed conservatively. One child has feeding difficulties; one has speech delay; 9 children (81.8%) have no known neurological/developmental sequelae. MSUD diagnosed clinically: 9 were diagnosed clinically. Average age of symptoms was 7 days (2 days- 5 months); median age of diagnosis 13 days (6 days-8.7 years). Median peak leucine level was 3395 umol/L (236–3849). 5 received dialysis (55.6%) and 4 (44.4%) were managed conservatively. Of this cohort, 3 (33.3%) have normal development and 6 (66.7%) have mild-severe neurological, developmental or behavioural abnormalities. Conclusions: NBS appears to have improved the outcome for children in this cohort. A high index of suspicion is encouraged for sick neonates admitted prior to NBS result becoming available. Further cohort analysis and standardised objective developmental follow up, would contribute to research in this important field.